Genome-wide association study and transcriptome analysis reveal the genetic basis underlying the environmental adaptation of plant height in a woody plant - Liu, Yao (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.